Cloud Economics and Enterprise Strategy: A bird eye’s view - Luxmi Dhirani, Lubna; Newe, Thomas; Nizamani, Shahzad (International Journal of Engineering and Technology, 2018)
Cloud Computing has enabled enterprises to focus on their core business by shifting their IT processes and operations on vendor managed public/hybrid clouds. Since the cloud offers numerous benefits such as: IT operational competence, flexibility, increased global reach, reduced cost, efficiency, customized applications and services making cloud computing the prime alternative in comparison to maintaining in-house operations. Migrating enterprises existing applications and services to a cloud if not properly managed may be susceptible to compatibility and orchestration-based risks. Cloud shifting may also lead to issues related to aligning enterprise strategy with IT and cloud services. This paper focuses on distinct aspects of Cloud Economics, aligning enterprise strategy with IT and Cloud Strategy and suggests the best methods to maintain Quality of Service and avoid Vendor lock-in and Service Level Agreement (SLA) based issues in the cloud ecosystem.Â